2004
DOI: 10.1016/j.jcrs.2003.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Retained anterior chamber cilium causing endophthalmitis after phacoemulsification

Abstract: An 81-year-old white man had uneventful cataract surgery by an experienced surgeon. Three days postoperatively, he presented with endophthalmitis and was treated in accordance with the standard departmental protocol. During the recovery, a curvilinear foreign body was identified and subsequently removed from the interior anterior chamber. Histological examination confirmed the foreign body as an eyelash. The patient improved to a final corrected visual acuity of 6/9. The relevant literature is reviewed, and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 5 publications
1
40
0
3
Order By: Relevance
“…9,14 Eyelashes are also a potential source of fibres. 6,10 It has been suggested that retained fibres may be difficult to detect intraoperatively for several reasons. These include glare from the operating microscope lights on the irrigating solutions, the low contrast afforded to the surgeon by the illumination of certain operating microscopes, and occasionally by obstruction of view through a focally oedematous cornea.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…9,14 Eyelashes are also a potential source of fibres. 6,10 It has been suggested that retained fibres may be difficult to detect intraoperatively for several reasons. These include glare from the operating microscope lights on the irrigating solutions, the low contrast afforded to the surgeon by the illumination of certain operating microscopes, and occasionally by obstruction of view through a focally oedematous cornea.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that the majority of retained intraocular fibres cause little or no inflammatory response. 1 In the absence of fibre-related adverse reactions/complications, such as endophthalmitis, 6,9,11,12,15 surgical removal of fibres, found postoperatively, currently remains unjustified.…”
Section: Fibres Found In the Eye During And After Pcs Ze Mcpherson Et Almentioning
confidence: 99%
See 3 more Smart Citations